Effects of Titanium Dioxide Nanoparticles on Chick Embryo: Immunomodulatory, Hepatic and Biochemical Alterations - Md. Sadequl Islam; Md. Nurul Amin; Mst. Deloara Begum (Veterinary Medicine and Science)
ABSTRACT Background The utilization of titanium dioxide nanoparticles (TiO2 NPs) has significantly increased across various industries. Objectives This study rigorously explored the impact of TiO2 NPs exposure on chicken embryos, focusing particularly on alterations in the immune system, liver functionality and key biochemical markers. Methods The study involved three groups of 30 eggs each, subjected to increasing doses of TiO2 NPs: Group C (control), Group T1 (150 µg/mL) and Group T2 (300 µg/mL). After 48 h of incubation, the eggs in Groups T1 and T2 each received an injection of 0.3 mL of the TiO2 NPs solution. In contrast, the eggs in the control group (Group C) were injected with 0.3 mL of saline solution. Histopathological changes were analysed using haematoxylin and eosin (H&E) staining, whereas amniotic fluid's biochemical properties were examined photometrically. The study also assessed the expression of immune genes (AvBD9, IL6 and IL8L2) through quantitative PCR. The evaluations included growth metrics, amniotic fluid biochemistry and histological analysis of the liver, caecal tonsil and bursa of Fabricius. Results The results revealed subcutaneous haemorrhage, significant reductions in total body weight and marked changes in biochemical markers, including urea, creatinine, alkaline phosphatase (ALP), aspartate aminotransferase (AST) and alanine aminotransferase (ALT), in the amniotic fluid of the groups treated with TiO2 NPs, compared to the control. Histological examinations indicated noticeable alterations in the liver, caecal tonsil and bursa of Fabricius following TiO2 NP exposure. These alterations were characterized by disruptions in cellular structures and variations in lymphocyte counts. Furthermore, a notable decrease in the expression of immunity genes, namely, AvBD9, IL8L2 and IL6, was observed in the TiO2 NP‐treated groups compared to the control. Conclusion The findings underscore the need for risk assessments of TiO2 NPs exposure due to its impact on development and immunity. Future research should explore its impact on neurodevelopment and degeneration.